2015
DOI: 10.1038/nmeth.3478
|View full text |Cite
|
Sign up to set email alerts
|

Efficient and quantitative high-throughput tRNA sequencing

Abstract: Despite its biological importance, transfer RNA (tRNA) could not be adequately sequenced by standard methods due to abundant post-transcriptional modifications and stable structure, which interfere with cDNA synthesis. We achieve efficient and quantitative tRNA sequencing using engineered demethylases to remove base methylations and a highly processive thermostable group II intron reverse transcriptase to overcome these obstacles (DM-TGIRT-seq). Our method should be applicable to investigations of tRNA in all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
586
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 462 publications
(644 citation statements)
references
References 20 publications
23
586
1
Order By: Relevance
“…Pan and co-workers also developed the DM-tRNA-seq method (Zheng et al 2015). They used AlkB to remove m1A, m3C, and m1G methylations, and a thermostable group II intron reverse transcriptase (TGIRT) to synthesis cDNA from highly structured tRNA.…”
Section: The State Of the Trna Population In The Cellmentioning
confidence: 99%
“…Pan and co-workers also developed the DM-tRNA-seq method (Zheng et al 2015). They used AlkB to remove m1A, m3C, and m1G methylations, and a thermostable group II intron reverse transcriptase (TGIRT) to synthesis cDNA from highly structured tRNA.…”
Section: The State Of the Trna Population In The Cellmentioning
confidence: 99%
“…Further structural and function analysis of ARS genes provide evidence that they have an impact on human life and contribute to the regulation and coordination processes in the mitochondria and nuclear genes simultaneously. Besides playing the major canonical role, their non-canonical pathways have a widespread impact; indeed, many researchers consider them as the hotspot of the regulation system [7][8][9][10][11][12][13]21,22]. Different factors are found to be associated with these gene mutations, like abnormal synthesis of enzyme, oxidative stress condition and other intrinsic and extrinsic causes.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, an extensive catalogue of diseases link with the pool of (n)tRNA, (mt)tRNA, ARS and ARS2 genes. The process of analyzing tRNA expression by deep sequencing is a recent favorite [22]. Emergence of deep sequencing to assess the genome-wide tissuespecific tRNA expression level has revealed that the (n) tRNAs and (mt) tRNAs exhibit distinct expression patterns, indicating that tRNAs might potentially be used as biomarkers for cancer.…”
Section: Introductionmentioning
confidence: 99%
“…In 2015, Pan's team described a potential way to quantify modifications, at least in another class of RNA called transfer RNAs 11 . The approach uses a reverse transcriptase that can read through the modifications efficiently, thereby capturing sequences downstream of the first modification it encounters.…”
Section: Moving Beyond Mappingmentioning
confidence: 99%